Comparison of offspring outcomes in women with and without epilepsy - Huali Luo; Xiaomin Mao; Shuli Zhu; Qiong Luo; Jiajia Fang; Qiwei Li (Annals of Clinical and Translational Neurology)
Abstract Objective The potential impact of antiseizure medications (ASMs) on abortion rate and bone metabolism in the offspring of pregnant women with epilepsy (WWE) is currently unknown. This research aimed to assess the potential risk by conducting a comparative analysis of bone metabolism‐related indicators in the offspring of WWE. Methods We retrospectively analyzed data from 83 epileptic parturients receiving antenatal care at our hospital and a co‐operative hospital from January 1, 2012, to December 31, 2021, comparing them to a control group of 249 parturients. The study analyzed and compared the two groups' growth parameters, including delivery mode, femoral length, biparietal diameter, and birth weight. Differences in femoral length, biparietal diameter, and birth weight among different ASM groups were also examined. Results WWE were more likely to undergo a cesarean section with a lower abortion rate (55.4% vs. 37.3%, P = 0.004). After adjusting for potential confounding variables, offspring femoral length in WWE was significantly reduced compared to the control group (6.812 cm vs. 6.923 cm, P < 0.0001). Moreover, those born to WWE using multiple ASMs had significantly reduced femoral and biparietal lengths compared to those whose mothers used a single ASM or none (P < 0.0001). Additionally, birth weight was significantly lower in offspring of WWE using multiple ASMs than those not using ASM (P < 0.05). Interpretation WWE experienced fewer abortions but worse negative offspring outcomes. The bone metabolism of the offspring of WWE was decreased and exhibited shortened femoral length, particularly in those on multiple ASMs.